Perlindungan UU No. 1 Tahun 1974 tentang Perkawinan kepada Calon Pengantin - Faisol Rizal (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
In marriage, some conventional fiqh literature stipulates that the authority to determine the marriage of the prospective bride is more dominant to the male side than the female party. For example, this is the opinion of Imam Syafi'i who allows the marriage of girls even though the girls are adults without the consent of the girls. In the Indonesian context, marriage must be based on the consent of the two prospective brides, which is one of the administrative requirements so that the marriage can take place. The methods used in this article is a qualitative approach to the library, where the focus is aimed against any reference about the religion, culture and islamic boarding school. The approach used is qualitative, which is a research procedure that describes the behavior of certain people, events, or places in detail and depth. While this type of research is literature. Namely, research that relies on reading sources, texts, and various information in the form of reading. In a different reference library research is research that is done to solve a problem that is based on a critical study of library materials and related research results presented in new ways.